Ditadura e justiça militar no Brasil : a atuação do Superior Tribunal Militar (1964-1980) - Silva, Angela Moreira Domingues da (2011)
The present study aims to analyzing the behavior of the Superior Military Court (STM in portuguese), the second instance of the Brazilian Military Justice, between the years of 1964 and 1980, in the process of construction of a new juridical order and in the judgment of military, political and political-military crimes. Since the coup of March 31st 1964, the STM has participated in the process of juridical-political punishment installed then. By editing the Institutional Act No. 2, in 1965, the Castelo Branco’s government has delegated to the Military Justice the trial of crimes against national security, seeking to solve problems generated by the tangle of legislation that defined by then the attributions of the STM e the Federal Supreme Court (STF in portuguese) in the judgment of offenses in the 'revolutionary' political conjuncture. According to the methodology adopted in this study, the Military Justice, as a whole, and the STM, in particular, have acted in this period by three distinct approaches: as a Corporative Justice (CJ), i.e., by judging military crimes; as a Regime Justice (RJ), directed towards the prosecution and trial of opponents to the regime, in cases of attacks against national security and against the administrative probity; and as a Political-corporative Justice (PCJ), by judging people charged with military offenses, but with a political motivation. Throughout the thesis, it was tried also to follow the manner the Court has behaved vis-à-vis the political and juridical changes that had inflicted in its structure and competence. As shown by this study, the impact of laws on the functioning of the STM is not immediate. The sluggishness of the justice and the procedural dynamics generated a lag between the governmental proposals and the judgments. One of the direct consequences of this phenomenon was the fact that the STM, mostly by acting as regime Justice, had to deal, simultaneously, with national security laws that would superpose and coexisted in the same juridical realm. It was verified that the decision-making pattern of the STM to judge each category tended to reproduce the decision of the Military Audits. This fact allows us to relativize the widespread thesis that the Court acted as a place of greater serenity and complacency towards those who were found guilty in the first instance.